CAUSAL FACTORS AND SOLUTIONS TO LEARNING DIFFICULTIES IN ARABIC IN CLASS XI IPS MADRASAH ALIYAH MUHAMMADIYAH 1 MEDAN-NORTH SUMATERA - Siti Rahma; Azizah Sabrina Gajah; Ernida Hasibuan; Sahkholid Nasution (Yayasan Haiah Nusratul Islam, 2025)
This research is motivated by the problem of students who have difficulty in learning Arabic. So the researcher raised the title related to